Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/esp.4251
|View full text |Cite
|
Sign up to set email alerts
|

Coast formation in an Arctic area due to glacier surge and retreat: The Hornbreen–Hambergbreen case from Spistbergen

Abstract: Glacierised coasts undergo faster geomorphic processes than unglaciated ones. We have studied changes of the coastal area in southern Svalbard with the glacier bridge between Torell Land and Sørkapp Land since the beginning of the 20th century. The existence of a continuous subglacial depression beneath the Hornbreen–Hambergbreen glacier system has been debated since the 1960s, with inconclusive results. In this study we assess both the subglacial topography and the bathymetry of Hornsund Fjord and Hambergbukt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 60 publications
2
60
1
Order By: Relevance
“…For the whole of Svalbard, we find that 13% of the glacierized area is grounded below sea level. Our results support the speculation that Sørkapp is a potential island separated by an ocean channel beneath Hornbreen and Hambergbreen (Grabiec et al, ). At present, the shallowest portion is covered by 180‐m‐thick ice.…”
Section: Resultssupporting
confidence: 92%
“…For the whole of Svalbard, we find that 13% of the glacierized area is grounded below sea level. Our results support the speculation that Sørkapp is a potential island separated by an ocean channel beneath Hornbreen and Hambergbreen (Grabiec et al, ). At present, the shallowest portion is covered by 180‐m‐thick ice.…”
Section: Resultssupporting
confidence: 92%
“…Terrigenous sediment input permits the formation of a subaqueous platform and the progradation of new coastal spit systems of more than 150 m in length seaward in a centennial timescale (Strzelecki et al, ). In South Spitsbergen, the retreat of the Hornbreen and its former tributaries (Hyrnebreen, Storbreen, Svalisbreen, Meddeleevbreen, and Chomjakovbreen) has contributed to the creation of Brepollen, the inner part of the Hornsund fjord (Grabiec et al, ). In Sørkapp, south‐eastern Spitsbergen, the front of three glaciers (Coryellebreen, Bevanbreen, and Kambreen) retreated by 600–800 m between 1936 and 2005 thereby generating large landscape modifications.…”
Section: Discussionmentioning
confidence: 99%
“…In nearby Hornsund the tides have an average amplitude of 0.75 m (Herman et al, 2019). Based on bathymetric profile interpolation, Moskalik et al (2013) divided the new bay into eight sub-basins, six of which consist of glacier valleys (Storbreen, Hornbreen, Svalisbreen, Mendelejevbreen, Chomjakovbreen and Hyrnebreen); one separate cove along the eastern shore of Treskelen; and one central open-water part which constitutes~30% of the bay area and has maximum water depths in excess of 140 m. The recent retreat of Hornbreen/Hambergbreen has also revealed evidence for a submerged channel Ostafin, 2014, 2019;Grabiec et al, 2018). Radar surveys across Hornbreen/Hambergbreen carried out by Grabiec et al (2018) revealed a 40 m-deep subglacial channel that, by 2055-2065, may evolve into a strait linking the Greenland and Barents seas (Brepollen and Hambergbukta, respectively) if current glacier retreat rates remain unchanged ( Figure 2).…”
Section: New Fjordsmentioning
confidence: 99%